Numerical studies of the combustion of fuel oil in the boiler furnace at reduced load - Ivantsov Aleksandr A. (MATEC Web of Conferences, 2014)
Relevance of the work due to the need to assess the effectiveness and reliability of the boiler units on reserve fuel after reconstruction associated with a change in the base fuel and approaches of numerical analysis. Analysis of physical and chemical processes in the furnace volume of boiler BKZ–210–140 operating on reserve fuel and rated load when using the Euler and Euler combined and Lagrangian modeling approaches. Results of the numerical modeling of the processes of aerodynamics, heat exchange, and combustion in the furnace volume.